Organomineral Fertilizer Is an Agronomic Efficient Alternative for Poultry Litter Phosphorus Recycling in an Acidic Ferralsol - de Melo Benites, Vinicius; Dal Molin, Sulian Junkes; Menezes, June Faria Scherrer; Guimarães, Getúlio Sousa; de Almeida Machado, Pedro Luiz Oliveira (Frontiers in Agronomy, 2022)
Brazil is a large phosphate importer due the high demand for this nutrient for grain cropping in very weathered soils. However, Brazil has an important poultry production which generates approximately 6.8 million m3.year-1 of organic residue containing phosphorus and other nutrients, increasing the risk of environmental harm. However, if well managed, poultry litter can be a valuable P source to crop growth in low fertile tropic soils. This paper summarizes the long-term agronomic efficiency of organomineral fertilizers in supplying P to soybean and soil P maintenance as a strategy for secondary P recycling. Three fertilizers were used as P source: organomineral based on raw poultry litter, organomineral based on composted poultry litter; and a mineral monoammonium phosphate. Five soybean crop seasons were conducted with annual P doses (20, 40, 60 and 80 kg ha-1 of P2O5) and a control without P application. After five crops, one additional soybean crop season was grown without P to evaluate the residual effect. Phosphorus concentration in leaves was evaluated in the first four seasons, and soil P availability in the first, third and fourth seasons. There was no difference in soybean grain yield, P concentration in leaves, and soil P availability as a function of the P sources in the first crop. Soybean grain yield only varied with the P rate applied after the second season, when the control had the lowest grain yield. After five crops, organomineral resulted in a slight but significant soybean yield gain compared to MAP at higher doses. The available soil P increased with the highest P dose and decreased in the control treatment over the time. The intermediate dose of 40 kg ha-1 P2O5 was enough to keep soil P level and lead to high soybean grain yield over the time, suggesting that the rate of applied P close to the P exportation by the grains has a long-term sustainable effect even in tropical soils, hence residual P stocks are used. It can be concluded that organomineral fertilizer is an efficient farm input that can be used for residue destination and nutrient recycling, especially in acid tropical soils.